Study on precast lightweight foamed concrete sandwich panel (PLFP) connection under flexural load - Mahadi, Nur Shahreena (2013)
Rapid growth of population has led to increasing demands on fast, affordable and quality housing. Nowadays, the construction industry in Malaysia has shifted from conventional method system towards Industrialized Building System (IBS). New technology investigation has been carried out to study the structural behavior of Precast Lightweight Foamed Concrete Sandwich Panel or PLFP as a load bearing wall system by previous researchers. In view of this, an experimental study is carried out to investigate the behavior of vertical connection for Precast Lightweight Foamed Concrete Sandwich Panel (PLFP). In this study, eight specimens comprised of plane surface connections and one panel as control without connection is cast and test under flexural loading until failure. The material used is foamed concrete with density1700 – 1800 kg/m2 as the overall fill and mortal as the connection in-fill. The objective of this study is to determine the load capacity and behavior of the connected panel with different length over depth ratio (aspect ratio of 0.83, 1.25 and 2.5). The behavior of the connection is studied through their load-deflection characteristic upon loading, load capacity, mode of failure and strain distribution. The relationship between aspect ratio and behavior of the panel were also observed. It was found that the higher aspect ratio, the more critical flexure failure at the connection occurred. The load capacity of the panel reduces by 30 to 60 percent of load with declination aspect ratio from 0.83 to 2.5.